Increased risk of endocrine autoimmunity in first-degree relatives of patients with autoimmune Addison's disease. Issue 1 (1st July 2020) - Fichna, Marta; Małecki, Piotr P; Młodzikowska, Mirela; Gębarski, Bolesław; Ruchała, Marek; Fichna, Piotr
Abstract: Objective: Autoimmune conditions tend to cluster in subjects with Addison's disease (AD) and probably also among their relatives. The aim of the study was to estimate the frequency of the endocrine gland-specific autoantibodies in first-degree relatives of patients with AD. Methods: Autoantibodies were investigated in 113 family members using RIA and ELISA assays. The control group comprised 143 age-matched volunteers. Results: Autoimmune diseases were diagnosed in 38.1% relatives. Hashimoto's thyroiditis was found in 20.3%, Graves' disease in 8.0%, vitiligo and type 1 diabetes in 3.5%, whereas AD, rheumatoid arthritis and atrophic gastritis with pernicious anaemia in 2.7% each. All studied antibodies except for islet antigen-2 ( P = 0.085) were significantly more frequent in AD relatives than in controls ( P < 0.05). Antibodies to 21-hydroxylase were detected in 6.2% relatives, thyroid peroxidase in 28.3%, thyroglobulin in 19.5%, glutamic acid decarboxylase in 8.0%, and zinc transporter-8 in 7.1%. Two and more autoantibodies were detected in 18.6% subjects. Significant gender difference was revealed only for aTPO, more common in female relatives ( P = 0.014; OR: 3.16; 95% CI: 1.23–8.12). Circulating autoantibodies were found more frequently in the relatives of affected males ( P = 0.008; OR: 3.31; 95% CI: 1.33–8.23), and in family members of patients with polyendocrine autoimmunity ( P = 0.009; OR: 3.55; 95% CI: 1.31–9.57). Conclusions: This study provides evidence of increased susceptibility for the endocrine autoimmunity, especially thyroid disease, in close relatives of patients with AD. Relatives of the male AD patients and of those with autoimmune polyendocrine syndrome are at particular risk and should undergo periodic screening for autoimmune endocrine disorders.